Diabetic ketoacidosis awareness among caregivers of type 1 diabetic children attending King Fahd Hospital, Khobar, Saudi Arabia - Yousef , Abdullah; Al-qahtani, Mohammad; Alfahhad, Lama; Alhalal, Zaineb; Alhadeeb, Luluwh; Alhatlani, Dina (Acta Biomedica Atenei Parmensis, 2024)
Background and aim: Diabetic ketoacidosis is a serious acute complication of diabetes mellitus. It is precipitated by infections, omission of insulin, and acute stress and illnesses. This life- threatening complication can be avoided by good control of diabetes and risk factors. Thus, parental awareness is of paramount importance. This study aims to determine the awareness level of the primary caregiver regarding the precipitating factors, signs and symptoms, and to discover the preventive methods taken to prevent the progression of the severity of diabetic ketoacidosis in type 1 diabetes children. Methods: Interview-based cross-sectional study conducted in King Fahd Hospital of the University, Saudi Arabia. Total number of participants was 173 caregivers and 183 children over 3 months period. Results: This study showed that 78.6% know the definition of diabetic ketoacidosis, 90.8% know that it is dangerous, 76.9% know that it has precipitating factors. The most recognized factor is skipping insulin doses 52.6%. The most recognized manifestations were nausea and vomiting (50.3%), abdominal pain (38.2%), and change in consciousness level (37.6%). 56.6% of caregivers don’t know the complications of diabetic ketoacidosis. 76.3% would go to the emergency room immediately if an episode happened. 71.7% would prevent diabetic ketoacidosis by insulin compliance. Conclusions: Diabetes education is crucial. Better level of understanding of the disease and its complications needs to be achieved, for diabetic ketoacidosis to be avoided. Caregivers must be aware about the risk factors, manifestations, and the proper action in emergency situations.